Family Violence in Adolescent Reactive Academic Behavior: a Systematic Review - Tapullima Mori, Calixto (2023)
Academic behavior currently represents an important variable to be addressed, it is greatly linked to the family environment; however, when the interaction is inadequate it can trigger reactive behaviors. The present study aimed to analyze the scientific literature in relation to reactive academic behavior in adolescents because of family violence. A literature review was carried out in five databases Scopus (392), PubMed (462), SciELO (5), Redalyc (2788) and Web of Science (118) with a total of 3765 articles, of which 18 documents were systematized that met the selection criteria established by the PRISMA model. The results showed that 22.2% of the articles came from Brazil, 16.7% from the United States, 11.1% from China, Mexico and Turkey, and 5.6% from countries such as Canada, Spain, Peru, Sweden and Thailand. The review shows that 100% were quantitative studies, 55.6% were cross-sectional; in addition, it has been found that violence in the family reaches levels above 60% and that its main manifestations are physical, verbal, and psychological abuse, which translates into behaviors of desertion, intimidation, and violent actions. In conclusion, family violence has a negative and significant effect on the reactive academic behavior of adolescents who have been exposed to situations of violence; finally, it is necessary to develop intervention and prevention strategies to improve the coexistence and well-being of adolescents.